Aproximació als contorns tonals del català central - Prieto i Vives, Pilar (Caplletra. Revista Internacional de Filologia, 1995)
The present study provides a preliminary description of a wide variety of pitch contours in Central Catalan, and shows that the phonological framework developed by Pierrehumbert (1980) and her colleagues successfully accounts for their relevant intonational distinctions. Compared to English, Central Catalan seems to make use of a wider inventory of pitch accents, namely, H*, L*, !L+H*, L*+H, H+L*, H+!, H*+L, and L+H*+H (a summary of the pitch accent plus boundary tone combinations is given at the end). As the model predicts, the relative alignment of the H and L levels with respect to the accented syllable triggers intonational oppositions in Catalan. For example, the distinction between an echo and a neutral pronunciation of a question like Què volia ahir en Joan? can be expressed with the use of H+L* vs. H*+L pitch accents respectively.